Predictive Model Prototype for Flooding in Caxias do Sul - Pereira, Eduardo Eberhardt; Notari, Daniel Luis (Anais da Escola Regional de Aprendizado de Máquina e Inteligência Artificial da Região Sul (ERAMIA-RS), 2025)
Heavy rainfall events that cause floods are natural and unavoidable, yet result in devastating damage to society and, therefore, must be studied to mitigate their impacts. This study proposes a predictive artificial intelligence model capable of classifying the occurrence of flood events using machine learning techniques, specifically, MLP neural networks. This research will be conducted in the city of Caxias do Sul, Brazil, using meteorological and hydrological data collected by Instituto Nacional de Meteorologia (INMET). The performance of the model will be evaluated using metrics such as accuracy and confusion matrix to explore recall and precision, and the explainability will be investigated using the Shapley Additive Explanations (SHAP) method.